A Social Dimension for a New Industrial Strategy for Europe - Cinzia Alcidi; Sara Baiocco; Francesco Corti (Intereconomics, 2021)
The impact of the COVID-19 pandemic has not been equal across economic sectors, age groups, education levels and employment status.
Keywords: 330; Industriepolitik; Arbeitsmarktpolitik; Sozialpolitik; EU-Staaten